Design of EWMA control chart for minimizing the proportion of defective units - Shamsuzzaman, Mohammad (2013)
Purpose – The exponentially weighted moving average (EWMA) control charts are widely used in industries for monitoring small and moderate process shifts. The purpose of this paper is to develop an algorithm for the optimization design of the EWMA chart (known as MD-EWMA chart).